Long-lasting stagnant equatorial plasma bubble event and the related scintillation over the Brazilian region. Issue 11 (1st December 2021) - Sousasantos, J.; Abdu, M.A.; Moraes, A.O.; Vani, B.C.; Silva, R.P.; Sobral, J.H.A.
Abstract: Diverse studies about equatorial plasma bubble structures and their relation with ionospheric scintillation have been performed in the last decades. Among many findings, the investigations usually reported dominant plasma bubble eastward velocity with a magnitude of few tens of m/s and larger amplitude scintillation for transionospheric signals aligned with these depleted structures. However, an uncommon long-lasting event with negligible average zonal drift prevailing for hundreds of minutes was registered over the Brazilian region, allowing a case study of the scintillation pattern under this particular condition. Data from ionosondes, all-sky imager (6300 Å filter), geostationary satellites and Global Navigation Satellite System were used here, covering the eastern portion of the Brazilian ionosphere. The results show that the scintillation was less intense than in other nights around the event, suggesting that larger plasma density gradients and sequential bubble structures seem to cause more severe scintillation scenario than the alignment condition alone, even though the last also contributes to worsen the scintillation effects. Regarding the stagnant bubble pattern, the results suggest prevailing E region Hall conductivity and equatorward wind as potential agents.